PERBANDINGAN ANALISA FUNDAMENTAL DAN TEKNIKAL DALAM PERDAGANGAN MATA UANG USD/JPY SETELAH PERISTIWA NON FARM PAYROLL - Limanto Angka, Andrew; Joyo Negoro Octavianus, Rony; Prasetyo, Daniel (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Katolik Widya Karya Malang, 2018)
This research was conducted to analyze the comparison of the results of the trading on the currency pair USD/JPY one hour after Non Farm Payroll?s release time using fundamental analysis,  Stochastic  Oscillator  technical  analysis,  ADX technical analysis, and combination of technical analysis during the period January 2015 to November 2016. Sampling technique used was the comparative analysis put forward by the Nazir (2005) where the purpose of the comparative analysis is to compare between the two groups in one or more variables. The research results showed that fundamental analysis has the return (in pips) which is the highest among the four others analysis. In the technical category, Stochastic Oscillator technical analysis has the highest number (in pips) of return than ADX technical analysis as well as combination of technical analysis.